Intramedulary locking nail elastic osteosynthesis in a cat femoral proximal fracture – case report - Lucena, D. V.F. [UNESP]; Dias, F. G.G.; Ferreira, D. R.C. [UNESP]; Rocha, T. A.S.S.; Campos, G. M.D.; Minto, B. W. [UNESP]; Dias, L. G.G.G. [UNESP] (FapUNIFESP (SciELO), 2024)
Intramedullary nails are the focus of scientific studies in small animal orthopedic surgery because the use of these materials in fractures of immature, small-sized patients, and in proximal bone regions is challenging. In this context, elastic osteosynthesis has been strongly advocated for the treatment of patients under four months of age. Therefore, the objective of this study was to report two cases of non-exposed complete fractures of proximal femurs in felines, resulting from trauma, both patientes under six months of age, treated with the elastic technique using a locked intramedullary nail. Both cases were treated through a surgical approach to the fracture site using the open, but don't touch method. In both cases, the bone consolidation process occurred in less than 60 days, along with satisfactory and early patient ambulation. Given the advocated osteosynthesis technique in the two patients and the promising results obtained, it is admitted that the use of locked intramedullary nails is a viable alternative for the treatment of proximal bone fractures in young felines.
Osteossíntese elástica com haste intramedular bloqueada em fratura proximal de fêmur em felino – relato de caso
Keywords: bone consolidation; cats; diaphyseal fracture; orthopedic implant